PENGEMBANGAN KEPEMIMPINAN MASA DEPAN - Nurul Amalia; Muhammad Rizki Syahputra; Shivva Amalia Khoiralla; Mochammad Isa Anshori (Bussman Journal : Indonesian Journal of Business and Management, 2023)
VUCA (Volatile, Uncertain, Complex, and Ambiguous) situations—situations where the world is very dynamic and difficult to predict—are created as a result of changes in reality. The purpose of this research is to discuss recent writings and studies regarding the characteristics of future leadership that are appropriate for adapting to change. Additionally, it offers a broad perspective on the future of leadership and stimulates reflection on leadership-related issues. This work information was collected through literature reflection and data analysis from various sources, including books, journals and websites related to leadership in the VUCA era. This information is then studied descriptively